Temperature, Precipitation and Relative Humidity Fluctuation of Makkah Al Mukarramah, Kingdom of Saudi Arabia (1985-2016) - Khan, Saifullah; Alghafari, Yasser (Transactions on Engineering and Computing Sciences, 2018)
The study presents the temperature, rainfall and relative humidity fluctuation of Makkah Al Mukarramah, Saudi Arabia for a time period of 1985-2016 in terms of general climatology, climate change, seasonal pattern and extreme weather condition. This is a city in the Tihamah plain of western Saudi Arabia, the capital of Makkah Province, birth place of Prophet Muhammad (PBUH) and holistic place in Islam. The factors that control the climate are surface water, coastal management, overgrazing, forestry, livestock, drought, desertification, industrialization, landuse change, tourism, altitude, location and marine influence etc. The mean monthly temperature of the city is 32?C having mean maximum of 38?C and mean minimum of 25 degree Celsius. The mean monthly temperature of the city shows an increase of one degree Celsius having -0.1?C decrease in maximum and -1.1?C in minimum temperature. Generally, there is a rise and fall in the temperature condition and shows periodic pattern after each ten years throughout the period. The total precipitation of the city is 189 millimeters (7.4inches); having an increase of 36millimeters (1.4inches) and shows an increasing trend. The relative humidity of the area is 46percent with an increase of 0.7percent. January and February are the wettest, while June and July are the hottest months of the city. The area shows an arid continental climate having two main seasons that is winter (5 months) and summer (7 months), which can further be sub-divided into four rainy seasons namely winter, post-winter, summer, and post-summer seasons. Annually, the temperature condition of the area rises from January to June, remains stable till September and slackens upto December. The heaviest rainfall of Makkah Al Mukarramah recorded in January, February and September and constitutes as wettest months of the year. The lowest rainfall of the city seems in June and July (driest months). To overcome the issue of climate change at Makkah Al Mukarramah, it is recommended to control wars, air pollution, improve forests, and to establish well canal system in the area.